Differential effects of attachment security on visual fixation to facial expressions of emotion in 14-month-old infants: an eye-tracking study - Joana L. Gonçalves; Marina Fuertes; Marina Fuertes; Susana Silva; Pedro Lopes-dos-Santos; Pedro Lopes-dos-Santos; Fernando Ferreira-Santos; Fernando Ferreira-Santos (Frontiers in Psychology, 2024)
IntroductionModels of attachment and information processing suggest that the attention infants allocate to social information might occur in a schema-driven processing manner according to their attachment pattern. A major source of social information for infants consists of facial expressions of emotion. We tested for differences in attention to facial expressions and emotional discrimination between infants classified as securely attached (B), insecure-avoidant (A), and insecure-resistant (C).MethodsSixty-one 14-month-old infants participated in the Strange Situation Procedure and an experimental task of Visual Habituation and Visual Paired-Comparison Task (VPC). In the Habituation phase, a Low-Arousal Happy face (habituation face) was presented followed by a VPC task of 6 trials composed of two contrasting emotional faces always involving the same actress: the one used in habituation (trial old face) and a new one (trial new face) portraying changes in valence (Low-Arousal Angry face), arousal (High-Arousal Happy face), or valence + arousal (High-Arousal Angry face). Measures of fixation time (FT) and number of fixations (FC) were obtained for the habituation face, the trial old face, the trial new face, and the difference between the trial old face and the trial new face using an eye-tracking system.ResultsWe found a higher FT and FC for the trial new face when compared with the trial old face, regardless of the emotional condition (valence, arousal, valence + arousal contrasts), suggesting that 14-month-old infants were able to discriminate different emotional faces. However, this effect differed according to attachment pattern: resistant-attached infants (C) had significantly higher FT and FC for the new face than patterns B and A, indicating they may remain hypervigilant toward emotional change. On the contrary, avoidant infants (A) revealed significantly longer looking times to the trial old face, suggesting overall avoidance of novel expressions and thus less sensitivity to emotional change.DiscussionOverall, these findings corroborate that attachment is associated with infants’ social information processing.